2007
DOI: 10.1136/bjo.2006.106468
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of sealed capsule irrigation using distilled water to prevent posterior capsule opacification: a prospective clinical randomised trial

Abstract: Background: We investigated long-term safety and efficacy of sealed capsule irrigation (SCI) during cataract surgery to prevent posterior capsule opacification (PCO). Methods: One eye of each of 17 patients (mean age: 70.1¡9.7 years) who presented with bilateral cataracts was randomly chosen for SCI treatment. After phacoemulsification, the capsular bag was vacuum sealed with the PerfectCapsule device (Milvella) followed by SCI using distilled water for two minutes. No vacuum loss occurred during irrigation. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 28 publications
0
41
1
1
Order By: Relevance
“…The substance that initially was intended to be used, DDW, was ineffective in humans or rabbits. 3,9 Mitomycin C or 5-FU has been reported to inhibit the proliferation of LECs and prevent PCO. 3,6 However, the use of these agents may be toxic to the ocular tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The substance that initially was intended to be used, DDW, was ineffective in humans or rabbits. 3,9 Mitomycin C or 5-FU has been reported to inhibit the proliferation of LECs and prevent PCO. 3,6 However, the use of these agents may be toxic to the ocular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The capsular bag then was flushed with distilled deionized water (DDW), and afterwards a hydrophilic intraocular lens (IOL) was implanted. Irrigation with DDW, however, did not prevent the development of PCO either in humans 9 or rabbits. 3 We observed a beneficial effect in preventing PCO when the sealed system was irrigated with 5-fluorouracil (5-FU) 50 mg/ml in an animal model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and monkeys [47,48] . Furthermore, different methods for drug application were tested [26,33,34,36,47,49] . Irrespective of the drug application, the effective local drug concentration must have been adequate to reduce the LEC viability to result in a long-term decrease in PCO.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study of human adults found that irrigation with distilled deionized water had no effect on PCO. 11 We previously found that 5-fluorouracil (5-FU) 50 mg/ml effectively killed LECs in a rabbit model. 12 We also showed that it is safe to use 5-FU with the device.…”
Section: Introductionmentioning
confidence: 99%